2011
DOI: 10.1309/ajcp45ssnaopxyxu
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Staining for TLE1 Distinguishes Synovial Sarcoma From Histologic Mimics

Abstract: Transducer-like enhancer of split 1 (TLE1) is overexpressed in synovial sarcomas. We investigated TLE1 expression by immunohistochemical analysis in a well-characterized series of synovial sarcomas and other mesenchymal tumors most commonly considered in the differential diagnosis. Whole tissue sections of 212 tumors were evaluated: 73 synovial sarcomas (23 biphasic, 28 monophasic, 22 poorly differentiated), 47 malignant peripheral nerve sheath tumors (MPNSTs), 49 solitary fibrous tumors (SFTs), 20 fibrosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
130
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(145 citation statements)
references
References 15 publications
7
130
4
1
Order By: Relevance
“…Biphasic examples of synovial sarcoma can be recognized by foci of epithelial/glandular differentiation. Synovial sarcoma shows positivity for TLE1 [24] and epithelial markers cytokeratin and EMA, even in the spindle cell component, but does not typically express SMA or HHF-35. Similar to prior studies [22,25], we observed frequent b-catenin expression in synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Biphasic examples of synovial sarcoma can be recognized by foci of epithelial/glandular differentiation. Synovial sarcoma shows positivity for TLE1 [24] and epithelial markers cytokeratin and EMA, even in the spindle cell component, but does not typically express SMA or HHF-35. Similar to prior studies [22,25], we observed frequent b-catenin expression in synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,[29][30][31] TLE1 shows promise as a marker of synovial sarcoma, but weak and variable expression can be seen in malignant peripheral nerve sheath tumors. [32][33][34][35] Consequently, genetic and molecular tests to demonstrate t(X;18) rearrangement or SS18-SSX fusion, respectively, have become routine at many specialized centers to confirm the diagnosis of synovial sarcoma. Although some controversy existed in the past regarding the specificity of this genetic abnormality, 36,37 the current consensus among sarcoma pathologists is that SS18-SSX fusions are highly specific for synovial sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…94 By immunohistochemistry, TLE1 shows moderate-tostrong, diffuse nuclear staining in the majority of synovial sarcomas (80-90%) (Figure 14). [95][96][97][98] TLE1 is a relatively specific marker for synovial sarcoma that can be helpful in differential diagnosis, as it is only positive in a small subset of malignant peripheral nerve sheath tumors and solitary fibrous tumors (usually with only weak staining), and it is consistently negative in Ewing sarcomas (which can be mistaken for poorly differentiated synovial sarcomas). 95,97 MUC4 is a high-molecular-weight transmembrane glycoprotein expressed on the surface of some glandular epithelial cell types.…”
Section: Lineage-restricted Transcription Factorsmentioning
confidence: 99%